Prevalence and molecular genetic features of epidermolysis bullosa in Krasnodar Krai - I. I. Pavlyuchenko; L. R. Gusaruk; E. E. Tekutskaya; I. T. Rubtsova (Кубанский научный медицинский вестник, 2020)
Background. Epidermolysis bullosa defi nes a clinically and genetically heterogeneous group of severe orphan disorders manifested with a congenital propensity for bullae (blisters) propagation on skin and mucous membranes of oesophagus, intestine, respiratory and urogenital systems. In the Russian Federation, its incidence rate is 1 per 50 –300 thousand of people. The actual disease prevalence in Krasnodar Krai is undefi ned. The genetic basis of this hereditary pathology has been studied insuffi ciently.Objectives. Epidemiological description of epidermolysis bullosa in Krasnodar Krai and detection of its chemical DNA signatures.Мethods. The prevalence of epidermolysis bullosa in Krasnodar Krai was studied with a relevant patient sample selected in an electronic archive of primary physician visits during 2010–2018. Chemical DNA signatures were detected as levels of blood serum 8-oxoguanine, a common marker of oxidative lesion. The 8-oxoguanine concentration was determined in ELISA assays with monoclonal antibodies. Statistical signifi cance was estimated with the chi-square and Mann–Whitney U test criteria for small samples.Results. A retrospective study revealed the total incidence rate of epidermolysis bullosa in Krasnodar Krai as 0.96 per 100,000 population, with prevalence in people aged under 30 years (75.5% of all patients, p < 0.01). In Krasnodar Krai, epidermolysis bullosa simplex accounts for 54.7% of total observed cases. Lethal form was diagnosed in 13.2%, and dystrophic type — in 5.7%. Diagnosis was incomplete as per type in 26.4% of patients. Serum 8-oxoguanine concentration in pathology comprised 14.8 ± 1.9 ng/mL, which exceeds 1.9-fold the control values of 7.7 ± 1.3 ng/mL (p < 0.01).Conclusion. The epidemiological profi le of epidermolysis bullosa in Krasnodar Krai was described. The disease prevalence, areal occurrence, predominant types and high-risk population groups were determined. A quarter of all patients had incomplete diagnosis as per the disease type. Elevated levels of 8-oxoguanine, the main product of DNA oxidation, indicate both genomic lesion and oxidative stress associated with epidermolysis bullosa.